Research on Shooting Action of Soccer Robot Based on Genetic-Fuzzy Algorithm - Wang Qiang; Zhang Jun-fu; Yang Yan-jun (2010 International Conference on Electrical and Control Engineering, 2010)
In order to improve the success rate of a soccer robot shooting a goal a new method of shooting action control based on genetic-fuzzy algorithm is presented in this paper. An MIMO fuzzy logical controller is established and the soccer robot is controlled by a set of fuzzy rules to complete shooting action in a real-time environment. To establish an optimum fuzzy logical controller a genetic algorithm is used to optimize the fuzzy rules and membership functions so as to increase the ability of the fuzzy logical controller to respond rapidly to the changes in the dynamic environment. We also take the kinematics model of wheeled mobile robot into account and use the speed of wheels directly as the output of fuzzy rules. Experimental results in simulation and vision-based remote brainless soccer robot system prove the method is correct and feasible.